1997
DOI: 10.1016/s0006-3495(97)78873-8
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of peptide nucleic acid and DNA decamers at electrically charged surfaces

Abstract: Adsorption behavior of peptide nucleic acid (PNA) and DNA decamers (GTAGATCACT and the complementary sequence) on a mercury surface was studied by means of AC impedance measurements at a hanging mercury drop electrode. The nucleic acid was first attached to the electrode by adsorption from a 5-microliter drop of PNA (or DNA) solution, and the electrode with the adsorbed nucleic acid layer was then washed and immersed in the blank background electrolyte where the differential capacity C of the electrode double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 36 publications
4
34
0
1
Order By: Relevance
“…Prolonged exposure to highly negative potentials does not desorb PNA molecules; although, under these conditions, almost all DNA molecules are removed from the surface. PNA adsorption increases with decreasing salt concentration, whereas DNA adsorption decreases under the same conditions (13). For DNA hybridization detectors, PNAs may serve as better probes than DNA.…”
Section: +mentioning
confidence: 95%
“…Prolonged exposure to highly negative potentials does not desorb PNA molecules; although, under these conditions, almost all DNA molecules are removed from the surface. PNA adsorption increases with decreasing salt concentration, whereas DNA adsorption decreases under the same conditions (13). For DNA hybridization detectors, PNAs may serve as better probes than DNA.…”
Section: +mentioning
confidence: 95%
“…The main purpose of this article is to show that electrochemical methods and particularly CPSA may provide information about the presence and accessibility of tyrosine, tryptophan and cystine/cysteine residues in peptides and proteins at nanomolar concentrations. In addition measurements of the adsorption/desorption signals [4,45,46] and AC impedance spectra [47] may provide information about the interaction of the biomolecule at the electrode surface. Studies of DNA protein interaction may be particularly interesting as it has been shown that not only peptides and proteins but also DNA yields its own reduction, oxidation and adsorption/desorption signals [33,36,38,45,48] which might change upon the formation of the DNA-protein complexes.…”
Section: Electrochemical Analysis In Protein-protein and Dna-protein mentioning
confidence: 99%
“…A DNA molecule (a genetic information carrier) is a double-stranded negatively charged polymer. DNA adsorption at negatively charged surface using self-assembled molecular monolayer or Peptide Nucleic Acid treatments are also investigated [9]. DNA changes its conformation through environmental interactions with the other components of the living cells [10,11].…”
Section: Introductionmentioning
confidence: 99%